ANALISIS MASLAHAH TERHADAP PRINSIP AT TARADHI DALAM DISTRIBUSI KEKAYAAN MELALUI WARIS DI DESA SUMBERHAJO PACITAN - Andri Riyanto; Subkhan Alimuddin (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines inheritance distribution practices in Sumberharjo Village, Pacitan, which are commonly carried out through family deliberation based on the principle of at-taradhi (mutual agreement). The study aims to understand inheritance distribution practices and analyze the value of maslahah within them. This research uses a qualitative method with a phenomenological approach. Data were collected through interviews, observations, and documentation. The findings show that the community prefers deliberation because it helps maintain harmony among siblings and prevent conflict after the death of parents. Agrarian economic conditions also influence inheritance distribution, particularly in preserving the productivity and economic value of agricultural land. However, the deliberation process does not always occur equally. The culture of pekewoh (reluctance) often causes some heirs, especially women, to remain silent or give in for the sake of family harmony. This study concludes that the practice of at-taradhi in inheritance distribution contains the value of maslahah because it preserves family harmony and the economic benefits of inherited property. However, equal participation among heirs remains important so that agreements truly arise from mutual willingness.